Experiences of registered nurses and nursing assistants during COVID-19: Work stress, stress appraisal, and workplace resources; A qualitative descriptive study - Gillian I. Adynski; Cassandra Dictus; Harry Adynski; Mary K. Killela; Elizabeth Allen Myer; Leah Morgan; Hayden Hmiel; Jessica Williams (PLoS ONE, 2026)
The COVID-19 pandemic severely disrupted healthcare systems, placing immense physical, emotional, and organizational strain on front line nursing staff, including registered nurses and nursing assistants. These professionals faced heightened stress due to increased virus exposure, global personal protective equipment (PPE) shortages, and rapidly changing protocols. This study sought to explore the experiences of registered nurses and nursing assistants working in inpatient care during the COVID-19 pandemic, focusing on workplace stressors and available or recommended resources to mitigate these challenges. Despite extensive documentation of elevated stress and burnout among nurses during COVID-19, little is known about how registered nurses and nursing assistants appraised specific workplace stressors and evaluated the adequacy of available organizational resources during the pandemic. Using a qualitative descriptive design, semi-structured interviews were conducted with 14 registered nurses and six nursing assistants from COVID-19 and non COVID units at a large academic medical center. Guided by Lazarus and Folkman’s Stress and Coping Model, the analysis identified a range of personal, interpersonal, organizational, and societal stressors. Personal stressors included long work hours, loss of loved ones to COVID-19, and feelings of isolation. Interpersonal stressors involved exposure risk, emotional strain from coworkers’ stress, and shifts in bedside roles. Organizational stressors encompassed staffing shortages, changes in protocols, and being called off shifts. Societal stressors included inconsistent public health messaging and concerns about protecting vulnerable family members. Participants emphasized the importance of authentic leadership and nursing-centered delivery of resources in addressing these stressors. Six key resource categories emerged: emotional support, staffing, safety, compensation, communication, and stress management. Findings highlight the critical role of nurse managers, effective communication, and staffing policies in mitigating workplace challenges. While rooted in a U.S. context, these insights may inform strategies to support nursing staff globally in future crises, reinforcing the need for tailored, sustainable approaches to front line caregiver well-being.